2021
DOI: 10.21203/rs.3.rs-486721/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application of Artificial Intelligence in Human Diagnosis and Public Health Management

Abstract: To improve the diagnostic efficiency and accuracy of corona virus disease 2019 (COVID-19), and to study the application of artificial intelligence (AI) in COVID-19 diagnosis and public health management, the computer tomography (CT) image data of 200 COVID-19 patients are collected, and the image is input into the AI auxiliary diagnosis software based on the deep learning model, "uAI the COVID-19 intelligent auxiliary analysis system", for focus detection. The software automatically carries on the pneumonia fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The results indicated that the two detection methods had the same range of lesion markers. However, the detection rate of the AI detection method based on DL was significantly higher than that of the manual detection method (P<0.05), while the false detection rate and missed diagnosis rate were remarkably lower than that of the manual detection method (P<0.05) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the two detection methods had the same range of lesion markers. However, the detection rate of the AI detection method based on DL was significantly higher than that of the manual detection method (P<0.05), while the false detection rate and missed diagnosis rate were remarkably lower than that of the manual detection method (P<0.05) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%